Pengaruh Rasio Ca/P Dan pH Pada Sintesa Hidroksiapatit Dari Kulit Kerang Darah Dengan Metode Hidrotermal Suhu Rendah - Pancasila Putri; Ahmad Fadli; Fajril Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Hydroxyapatite (HA) is widely used types of biomaterials for bone implants, surgery hard tissue and bone regeneration. The purpose of this research was to determine the effect of Ca/Pratio and pH on the synthesis of hydroxyapatite from sea shells with a low temperature hydrothermal method. CaO powder produced through calcination process of sea shells at atemperature of 1000°C for 24 hours. Then CaO powder as much as 45.91 grams dissolved in 600 ml of water and NH4H2PO4 added with ratio Ca/P 0.67, 1.67 and 2.67 and pH adjusted with variation 4, 6 and 9, then heated at 90°C until form a pasta. The pasta is then dried in the oven at 120°C and calcined at a temperature of 900°C for 1 hour. The results showed that increasing the ratio Ca/P and pH causes the diameter of HA crystals formed smaller with diameter at ratio Ca/P 2,67 and pH 9 was 52,32 nm. FTIR analysis showed peaks of PO4 3- and OH- that means the hydroxyapatite is formed. HA at ratio Ca/P 2,67 and pH 9 had the biggest %yield that was 77,73%.Keywords: Hydrothermal, Hydroxyapatite, Sea shells.